Analysis of Human Relationships and Physical Work Environment on Work Ethic - Muhtarom, Asrori; Mulia Z, Faizal; Komariah, Kokom (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The purpose of this study is to describe human relations, physical work environment, and work ethic. Then to analyze the effect of human relations, physical work environment on employee work ethic at Perumda Air Minum Tirta Jaya Mandiri Sukabumi Regency. This study uses associative research methods with a quantitative approach. The population is all employees of Perumda Air Minum Tirta Jaya Mandiri totaling 58 people using saturated sampling. The type of data used is primary and secondary data, the measurement of this study using a semantic differential scale. In this research analysis technique, namely using validity test, reliability test, correlation coefficient analysis, coefficient of determination analysis, multiple linear regression analysis, research model testing (F test), and hypothesis testing (T test). Based on the results of the study, it is obtained that the relationship between the variables of Human Relations and the Physical Work Environment on Work Ethic is 0.874, including the criteria for a very strong relationship, the magnitude of the influence of Human Relations on Work Ethic is 0.667, and the magnitude of the influence of the Physical Work Environment on Work Ethic is 0.615 or 76.4% while the remaining 23.6% is influenced by other factors not included in this study.